2016
DOI: 10.1902/jop.2016.160144
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 0.12% Chlorhexidine Gluconate for Non‐Surgical Treatment of Peri‐Implant Mucositis

Abstract: Both isolated mechanical therapy and its association with 0.12% chlorhexidine mouthwash reduced peri-implant mucositis. Therefore, 0.12% of chlorhexidine was not more effective than placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
3
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(96 citation statements)
references
References 37 publications
(62 reference statements)
1
79
3
8
Order By: Relevance
“…These percentages, however, decreased to 9.6% at 6 months in the control group. These results with the conventional treatment to manage PM were markedly inferior to those reported previously in the literature ranging between 38% and 83.3% (Hallstrom, Persson, Lindgren, Olofsson, & Renvert, ; Heitz‐Mayfield et al, ; Menezes, Fernandes‐Costa, Silva‐Neto, Calderon, & Gurgel, ; Pulcini et al, ; Riben‐Grundstrom et al, ). In contrast, in the test group, this percentage increased to 66.6%.…”
Section: Discussioncontrasting
confidence: 65%
“…These percentages, however, decreased to 9.6% at 6 months in the control group. These results with the conventional treatment to manage PM were markedly inferior to those reported previously in the literature ranging between 38% and 83.3% (Hallstrom, Persson, Lindgren, Olofsson, & Renvert, ; Heitz‐Mayfield et al, ; Menezes, Fernandes‐Costa, Silva‐Neto, Calderon, & Gurgel, ; Pulcini et al, ; Riben‐Grundstrom et al, ). In contrast, in the test group, this percentage increased to 66.6%.…”
Section: Discussioncontrasting
confidence: 65%
“…When compared with the previous study by Menezes et al, the percentage of reduction of bleeding on probing worsened, while the probing depth remained stable over the long term. The fact that we did not use chlorhexidine in association with peri‐implant support therapy, and used only mechanical therapy and oral hygiene guidance, may be a possible explanation for this outcome, as well as the longer time interval between control visits.…”
Section: Discussioncontrasting
confidence: 65%
“…To obtain data, all subjects were submitted to anamnesis and periodontal clinical examination, composed of visible plaque index (VPI), gingival bleeding index (GBI), and full periodontal chart, according to the method applied by Menezes et al All subjects signed an informed consent form and were followed for 54 months. For data analysis, all information was collected and inserted in a database using the Statistical Package for Social Sciences (SPSS), version 22.0.…”
Section: Methodsmentioning
confidence: 99%
“…Paolantonio et al reported that the application of a 1% chlorhexidine gel could reduce bacterial counts, without interfering with specific pathogens. These findings imply that the number of bacteria present cannot be used to predict the prognosis of peri‐implantitis …”
Section: Discussionmentioning
confidence: 99%